Nanometer silicon negative electrode material with porous structure and preparation method and application of nanometer silicon negative electrode material

By molten salt electrolytic technology, electrolytic and dehydration treatment of photovoltaic silicon cutting waste, prepare porous structure nano -silicon negative materials, solve the lack of porous silicon preparation in existing technologies and the impact of the electrochemical performance of lithium battery in existing technologies. Economic lithium -ion battery negative material preparation.

CN119352048APending Publication Date: 2025-01-24KUNMING UNIV OF SCI & TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411480581.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems such as uneven pore structure, poor stability, and low yield when preparing porous silicon structures. It is difficult for traditional dealloyment methods to accurately remove specific elements, which affects the electrochemical performance of lithium batteries.

Method used

The molten salt electrolysis technology uses electrolysis of photovoltaic silicon cutting waste. The SI-ME alloy is formed through the initial electrolytic and high-frequency pulse electrolytes, and then the alloy uniformity treatment and electrolytic alloy alloy treatment are finally performed. In the end

Benefits of technology

A multi -sanali -silicon negative material with high -ratio surface area has been achieved, reducing the accumulation and processing cost of waste materials, and improving the cycle stability and safety of lithium -ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352048A_ABST
    Figure CN119352048A_ABST
Patent Text Reader

Abstract

The invention provides a porous structure nanometer silicon negative electrode material and a preparation method and application thereof, and relates to the technical field of lithium ion battery silicon negative electrode materials. The preparation method comprises the following steps: mixing the photovoltaic silicon cutting waste with molten salt, and sequentially carrying out primary electrolysis and high-frequency pulse electrolysis in an electrolysis container provided with an auxiliary electrode to obtain Si-Me alloy; sequentially carrying out alloy homogenization treatment, electrolytic dealloying treatment and annealing treatment on the Si-Me alloy to obtain the nano silicon negative electrode material with the porous structure; the auxiliary electrodes are arranged on the inner wall and the bottom of the electrolysis container, and the auxiliary electrodes on the inner wall and the bottom do not make contact. By introducing the auxiliary electrode, the electrolytic efficiency can be improved, and side reactions can be reduced; by utilizing the existing molten salt environment, the metal Me in the alloy can be removed only by adjusting the electrolysis voltage, so that the metal Me is converted into ions again to return to the molten salt, a porous silicon structure is generated, the damage to materials is reduced, and the use and energy consumption of chemical reagents are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery silicon negative electrode materials, and in particular to a porous structure nano silicon negative electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the photovoltaic industry, the transition of photovoltaic silicon cells to large size and thin slices and from polycrystalline silicon to monocrystalline silicon has become a mainstream trend. However, in the process of cutting silicon ingots into thin slices of silicon cells, 30-40% of silicon cutting debris will be generated. The purity of these silicon debris is extremely high (more than 99.9999%), the particle size is extremely small, and they exist in the form of nano-micron flakes. However, since the surface of silicon waste is easy to react with oxygen in the air to form a silicon oxide layer, it increases the difficulty of recycling silicon cutting waste. This may produce a large amount of accumulated silicon waste, which is easy to cause harm to the environment. Therefore, how to efficiently recycle and utilize these photovoltaic silicon cutting wastes has become the focus of current research. As a negative electrode material for lithium-ion batteries, the theoretical specific capacity of silicon (about 4200mAh / g) is more than ten times that of current commercial graphite (372mAh / g). However, silicon will undergo a volume expansion of about 300% during the charge and discharge process, resulting in the pulverization of active materials and the failure of electrode structures, which seriously affects the cycle life of lithium batteries. Therefore, how to alleviate the volume expansion of silicon negative electrodes is one of the key challenges in silicon-based material research. Studies have shown that porous silicon can effectively alleviate the volume expansion of silicon during charging and discharging, and also significantly increase the specific surface area of ​​silicon, enhance the contact with the electrolyte, and improve the electrochemical performance of silicon materials. Therefore, the development and optimization of porous silicon materials is of great significance for the realization of high-performance silicon-based lithium-ion batteries.

[0003] Existing methods for preparing porous silicon structures include chemical vapor deposition, chemical etching, template method and thermal decomposition. These methods usually involve complex chemical reactions and operating procedures, the required raw materials and equipment are expensive, and the prepared porous silicon often has problems such as uneven pore structure, poor stability, and low yield. These shortcomings seriously limit the commercial application of porous silicon. Therefore, it is of great practical significance to find an economical, efficient and environmentally friendly method for preparing porous silicon, especially using photovoltaic silicon waste. Molten salt electrolysis technology is a green, low-cost and efficient material preparation method. This technology is used to electrolyze photovoltaic silicon cutting waste. By controlling the electrolysis conditions, not only can the oxide layer on the surface of the silicon waste be reduced to pure silicon, but also the reduced cations in the molten salt can be formed at the cathode at a certain electrolysis temperature. The traditional dealloying methods mainly include chemical leaching and mechanical separation. Chemical leaching usually relies on the reaction of strong acid or strong base with alloy. This method has poor selectivity and is difficult to accurately remove specific elements. It is easy to damage or dissolve silicon materials, thus affecting the purity and structure of porous silicon. Mechanical separation often involves physical operations such as crushing and grinding, which can easily cause physical damage to the material, affect the microstructure and mechanical strength of porous silicon, and is difficult to accurately separate different elements. Especially when dealing with complex alloys, the impurity removal efficiency is low, which seriously affects the electrochemical performance of lithium batteries. Therefore, finding a method for efficient dealloying and obtaining stable electrochemical performance has become a problem that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to provide a porous structure nano-silicon negative electrode material and its preparation method and application, so as to solve the problem that when preparing porous structure silicon material by chemical leaching or mechanical separation to remove metal in silicon-Me alloy, the material is easily damaged, the microstructure and mechanical strength of the material are affected, and it is difficult to accurately remove specific elements and separate different elements. The use of the porous structure silicon material as an electrolytic material will seriously affect the electrochemical performance of lithium batteries.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a porous structure nano-silicon negative electrode material, comprising the following steps:

[0007] 1) Mixing photovoltaic silicon cutting waste with molten salt, and sequentially performing primary electrolysis and high-frequency pulse electrolysis in an electrolysis container provided with an auxiliary electrode to obtain Si-Me alloy;

[0008] 2) performing alloy homogenization treatment on Si-Me alloy;

[0009] 3) placing the Si-Me alloy after the alloy homogenization treatment in an electrolytic container again for electrolytic dealloying treatment, and then annealing to obtain a porous structure nano-silicon negative electrode material;

[0010] The auxiliary electrodes are arranged on the inner wall and the bottom of the electrolysis container, and the auxiliary electrodes on the inner wall and the bottom are not in contact.

[0011] Preferably, the auxiliary electrode is made of one or more of molybdenum, titanium, platinum, tungsten, tantalum, zirconium or nickel metal materials;

[0012] The anodes of the primary electrolysis, high-frequency pulse electrolysis and electrolytic dealloying treatment are independently made of carbon materials, and the cathodes are independently made of molybdenum, platinum, tungsten or zirconium materials.

[0013] Preferably, the particle size of the photovoltaic silicon cutting waste in step 1) is 0.5 to 10 μm;

[0014] The molten salt is a metal halide;

[0015] The mass ratio of the photovoltaic silicon cutting waste to the molten salt is 1-20:100-500.

[0016] Preferably, the temperature of the initial electrolysis in step 1) is 500-1200° C.;

[0017] The voltage of the initial electrolysis is greater than the theoretical decomposition voltage of the oxide corresponding to the cation in the molten salt at the electrolysis temperature and less than the minimum electrolysis voltage required for the cation to be reduced to its simple substance;

[0018] The time of the initial electrolysis is 0.5 to 4 hours;

[0019] The auxiliary electrode potential of the initial electrolysis is 2.0-3.8V.

[0020] Preferably, the temperature of the high-frequency pulse electrolysis in step 1) is 500-1200° C.;

[0021] The minimum potential of the high-frequency pulse electrolysis is 0.01 to 2 V greater than the theoretical decomposition voltage of cations in the molten salt, and the potential difference between the maximum potential and the minimum potential is 0.1 to 4 V;

[0022] The time of the high-frequency pulse electrolysis is 1 to 6 hours, and the duration of each band of the high-frequency pulse electrolysis is 25 to 50 seconds;

[0023] The auxiliary electrode potential of the high-frequency pulse electrolysis is 2.5-5V.

[0024] Preferably, the alloy homogenization treatment in step 2) includes a first stage of preliminary homogenization treatment, a second stage of target phase homogenization treatment, and a third stage of cooling treatment;

[0025] The heating rate of the first stage of preliminary homogenization treatment is 1-5°C / min, the target temperature is 650-110°C, and the holding time is 30-300min;

[0026] The temperature change rate of the target phase homogenization treatment in the second stage is 1-5°C, the target temperature is 700-1200°C, and the holding time is 20-200min;

[0027] The cooling rate of the third stage cooling treatment is 1-5°C / min, and the target temperature is 500-1200°C.

[0028] Preferably, the temperature of the electrolytic dealloying treatment in step 3) is 500-1200° C., the electrolytic voltage of the electrolytic dealloying treatment is 0.5-3.8 V, and the time of the electrolytic dealloying treatment is 0.5-6 h;

[0029] The potential of the auxiliary electrode in the electrolytic dealloying treatment is 1.5 to 3.0V.

[0030] Preferably, the annealing temperature in step 3) is 300-900° C., and the annealing time is 60-300 min.

[0031] The present invention also provides a porous nano-silicon negative electrode material prepared by the above preparation method.

[0032] The present invention also provides an application of the porous nano-silicon negative electrode material in a negative electrode material for a lithium battery.

[0033] The present invention has at least the following beneficial effects:

[0034] (1) The present invention utilizes cheap and readily available photovoltaic silicon cutting waste to prepare a porous structure nano-silicon negative electrode material with a high specific surface area through a simple electrochemical method, thereby reducing the accumulation and treatment costs of waste materials. It also provides a new type of high-performance negative electrode material for the lithium-ion battery field, realizes the efficient recycling of silicon waste, and has significant economic value.

[0035] (2) The present invention not only effectively improves the ion migration efficiency during the electrolysis process by introducing an independent auxiliary electrode and a high-frequency pulse potential, but also ensures the uniformity of the electrolysis reaction. The precise potential control of the auxiliary electrode generates an additional electric field, which further optimizes the movement path of cations in the molten salt to the cathode, improves the electrolysis efficiency and reduces the side reactions that may occur during the electrolysis process. The high-frequency pulse potential enhances the reaction activity and reduction efficiency during the electrolysis process by periodically changing the electric field, which helps to form a more uniform Si-Me alloy structure. The application of this combination not only improves the electrolysis efficiency, but also improves the microstructural quality of the alloy material, providing a more stable and high-quality precursor material for the subsequent dealloying process. The Si-Me alloy prepared by this method has a short process flow and low energy consumption, and is easier to achieve continuous low-cost large-scale industrial production.

[0036] (3) The present invention cleverly utilizes the redox characteristics of molten salt electrolysis. First, by utilizing the reduction characteristics of molten salt electrolysis, the oxide layer on the surface of silicon waste is successfully removed and the generation of alloyed materials is achieved. In the subsequent dealloying process, the existing molten salt environment is cleverly utilized, and the metal Me in the alloy loses electrons and undergoes an oxidation reaction by simply adjusting the electrolysis voltage, and is reconverted into Me ions and returns to the molten salt. As the metal in the Si-Me alloy is effectively removed, the porosity of Si-Me gradually increases, and a porous silicon structure is generated when the electrochemical dealloying process is completed. Compared with traditional dealloying methods, this electrolytic dealloying not only reduces damage to the material, but also reduces the use of chemical reagents and energy consumption, reduces the risk of environmental pollution, and improves production efficiency, showing significant advantages in selectivity, environmental protection and control accuracy, which is in line with the trend of green manufacturing.

[0037] (4) The porous structure nano-silicon negative electrode material prepared by the present invention can not only effectively alleviate the volume expansion problem caused by the insertion and extraction of lithium ions, but also accelerate the migration rate of lithium ions during the extraction and extraction process, reduce the charge transfer resistance, and thus significantly improve the cycle stability of lithium ion batteries and the safety of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram of the electrolysis device and electrolysis process of the present invention, Figure 1 (a) is a schematic diagram of the electrolysis process of the initial electrolysis and high-frequency pulse electrolysis in step 1). Figure 1 (b) is a schematic diagram of the electrolytic de-alloying in step (3); wherein 1 is an electrolytic container, 2 is an auxiliary electrode, 3 is an anode, 4 is a cathode, and 5 is a molten salt and photovoltaic silicon cutting waste;

[0039] Figure 2 This is a SEM image of photovoltaic silicon cutting waste in Example 1;

[0040] Figure 3 is a graph showing the change of high-frequency pulse electrolysis voltage over time in Example 1;

[0041] Figure 4 This is a SEM image of the porous nano-silicon negative electrode material prepared in Example 1;

[0042] Figure 5 The XRD diagrams of the alloyed product after alloy homogenization treatment and the product after electrolytic dealloying treatment in Example 1;

[0043] Figure 6 This is a test diagram of the cycle performance of a half-cell prepared by conducting electrochemical performance tests on porous structure nano-silicon negative electrode materials and photovoltaic silicon cutting waste in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0044] The present invention provides a method for preparing a porous structure nano-silicon negative electrode material, comprising the following steps:

[0045] 1) Mixing photovoltaic silicon cutting waste with molten salt, and sequentially performing primary electrolysis and high-frequency pulse electrolysis in an electrolysis container provided with an auxiliary electrode to obtain Si-Me alloy;

[0046] 2) performing alloy homogenization treatment on Si-Me alloy;

[0047] 3) placing the Si-Me alloy after the alloy homogenization treatment in an electrolytic container again for electrolytic dealloying treatment, and then annealing to obtain a porous structure nano-silicon negative electrode material;

[0048] The auxiliary electrodes are arranged on the inner wall and the bottom of the electrolysis container, and the auxiliary electrodes on the inner wall and the bottom are not in contact.

[0049] In the present invention, the auxiliary electrode is made of one or more of molybdenum, titanium, platinum, tungsten, tantalum, zirconium or nickel metal materials.

[0050] In the present invention, the anodes of the primary electrolysis, high-frequency pulse electrolysis and electrolytic dealloying treatment are independently made of carbon materials, and the cathodes are independently made of molybdenum, platinum, tungsten or zirconium materials.

[0051] In the present invention, the electrolysis container is preferably a high temperature resistant crucible made of graphite, aluminum oxide, zirconium oxide, molybdenum, magnesium oxide or boron nitride.

[0052] In the present invention, the diameter ratio of the cathode, anode and electrolytic container is 1-80:1-50:5-800, preferably 10-60:10-40:100-600, more preferably 20-40:20-30:200-400, and more preferably 25-30:22-25:250-300.

[0053] In the present invention, the distance between the anode and the cathode is 0.1 to 10 times the diameter of the anode, preferably 3 to 8 times the diameter of the anode, and more preferably 5 to 7 times the diameter of the anode.

[0054] In the present invention, the particle size of the photovoltaic silicon cutting waste in step 1) is 0.5 to 10 μm, preferably 0.8 to 8 μm, more preferably 1.2 to 6 μm, and more preferably 1.5 to 4 μm.

[0055] In the present invention, the molten salt is a metal halide, preferably NaCl, KCl, LiCl, CaCl 2 MgCl 2 、AlCl 3 、BaCl 2 、MnCl 2 、ZnCl 2 , CuCl 2 、SrCl 2 、NaF、KI、LiI、NaI、CaF 2 MgF 2 , FeF 2 , AlBr 3 、BaCl 2 、NaBr、KBr、MnBr 2 、ZnF 2 ,CrF 2 、NiF 2 ,CuF 2 、TiF 4 , MnF 2 , ZrF 4 or SrF 2 One or more of the .

[0056] In the present invention, the initial electrolysis and high-frequency pulse electrolysis are preferably carried out under an inert gas atmosphere, wherein the inert gas is independently one or more of nitrogen, argon or helium, and the flow rate of the inert gas is 5 to 50 mL / min, preferably 10 to 40 mL / min, and further preferably 20 to 30 mL / min.

[0057] In the present invention, the mass ratio of the photovoltaic silicon cutting waste to the molten salt is 1-20:100-500, preferably 3-15:200-400, more preferably 5-12:250-350, and more preferably 8-10:280-320.

[0058] In the present invention, the temperature of the initial electrolysis in step 1) is 500-1200°C, preferably 600-1100°C, more preferably 700-1000°C, and even more preferably 800-900°C.

[0059] In the present invention, the voltage range of the initial electrolysis is set to be greater than the theoretical decomposition voltage of the oxide corresponding to the cation in the molten salt at the electrolysis temperature and less than the minimum electrolysis voltage required for the cation to be reduced to its simple substance; in a multi-cation system, the decomposition voltage of each cation can be calculated by referring to its standard electrode potential and combining the Nernst equation, considering different concentrations and temperature conditions, and calculating its actual reduction potential. For a variety of molten salt systems, the decomposition voltage range of the system is determined by the minimum decomposition voltage of the cation with the lowest reduction potential. At the same time, the upper limits of the reduction potentials of other cations are comprehensively considered, and the actual decomposition voltage range of the electrolysis system is determined through theoretical calculations and electrochemical experimental verification.

[0060] In the present invention, the time of the initial electrolysis is 0.5 to 4 hours, preferably 1 to 3.5 hours, more preferably 1.5 to 3 hours, and more preferably 2 to 2.5 hours.

[0061] In the present invention, the auxiliary electrode potential of the primary electrolysis is 2.0 to 3.8 V, preferably 2.2 to 3.5 V, more preferably 2.5 to 3.2 V, and even more preferably 2.8 to 3.0 V.

[0062] In the present invention, the temperature of the high-frequency pulse electrolysis in step 1) is 500-1300°C, preferably 600-1200°C, more preferably 700-1100°C, and even more preferably 800-1000°C.

[0063] In the present invention, the minimum potential of the high-frequency pulse electrolysis is 0.01 to 2 V greater than the theoretical decomposition voltage of cations in the molten salt, preferably 1.5 to 1.8 V, more preferably 0.8 to 1.5 V, and more preferably 1 to 1.3 V; and the potential difference between the maximum potential and the minimum potential is 0.1 to 4 V, preferably 0.5 to 3.5 V, more preferably 1 to 3 V, and more preferably 2 to 2.5 V.

[0064] The theoretical decomposition voltage of the cations in the molten salt can be obtained by consulting the standard electrode potential and calculating it in combination with the Nernst equation; when there are multiple cations in the molten salt, the theoretical decomposition voltage of each cation is first calculated by consulting its standard electrode potential and combining it with the Nernst equation, and the cation with the lowest reduction potential is selected as the basis for determining the minimum theoretical decomposition voltage of the system.

[0065] In the present invention, the time of the high-frequency pulse electrolysis is 1 to 6 hours, preferably 2 to 5 hours, and more preferably 3 to 4 hours; the high-frequency pulse electrolysis is to use high and low voltages to alternately electrolyze the molten salt and photovoltaic silicon cutting waste systems; the duration of each band of the high-frequency pulse electrolysis is 25 to 50 seconds, preferably 30 to 45 seconds, and more preferably 35 to 40 seconds.

[0066] In the present invention, the auxiliary electrode potential of the high-frequency pulse electrolysis is 2.5 to 5V, preferably 3 to 4.5V, more preferably 3.5 to 4V, and even more preferably 3.8V.

[0067] In the present invention, during the initial electrolysis and high-frequency pulse electrolysis, the auxiliary electrode on the inner wall of the electrolysis container is connected to the positive electrode of the power supply, and the auxiliary electrode at the bottom of the electrolysis container is connected to the negative electrode of the power supply.

[0068] In the present invention, the difference in potential between the auxiliary electrode and the cathode during the initial electrolysis and high-frequency pulse electrolysis is independently 0.1 to 6 V, preferably 0.5 to 5 V, further preferably 1 to 4 V, and more preferably 2 to 3 V, which can guide the cations in the molten salt to move more effectively to the cathode during the electrolysis process.

[0069] In the present invention, the alloy homogenization treatment in step 2) includes a first stage of preliminary homogenization treatment, a second stage of target phase homogenization treatment and a third stage of cooling treatment.

[0070] In the present invention, the heating rate of the first stage preliminary homogenization treatment is 1-5°C / min, preferably 2-4°C / min, and more preferably 2-3°C / min; the target temperature is 650-1100°C, preferably 700-1050°C, and more preferably 750-1000°C; the holding time is 30-300min, preferably 120-240min, more preferably 150-210min, and more preferably 180min.

[0071] A slower heating rate can effectively avoid thermal stress caused by excessive temperature gradient inside the alloy, and the preliminary homogenization treatment can promote the preliminary homogenization of different phases.

[0072] In the present invention, the temperature change rate of the second stage target phase homogenization treatment is 1-5°C, preferably 2-4°C / min, and more preferably 2-3°C / min; the target temperature is 700-1200°C, preferably 750-1180°C, and more preferably 800-1150°C; the insulation time is 20-200min, preferably 40-150min, and more preferably 60-120min.

[0073] Slower heating and cooling rates help to suppress abnormal grain growth.

[0074] In the present invention, the temperature change rate of the third stage cooling treatment is 1-5°C / min, preferably 2-4°C / min, and more preferably 2-3°C / min; the target temperature is 500-1200°C, preferably 600-1050°C, and more preferably 650-900°C.

[0075] Slowly cool or heat to the final electrolysis temperature. The temperature of electrolytic de-alloying is lower than the melting point of the alloy but sufficient to promote the oxidation reaction of the Me element. The slower temperature change rate can avoid the formation of new phases or microcracks caused by thermal stress, ensuring that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0076] In the present invention, the homogenization treatment is preferably carried out under an inert atmosphere, wherein the inert atmosphere is one or more of nitrogen, argon or helium, and the flow rate of the inert gas is 5 to 35 mL / min, preferably 10 to 30 mL / min, and more preferably 15 to 25 mL / min.

[0077] In the present invention, the temperature of the electrolytic dealloying treatment in step 3) is 500-1200°C, preferably 600-1100°C, further preferably 700-1000°C, and more preferably 800-900°C; the electrolysis voltage of the electrolytic dealloying treatment is 0.5-3.8V, preferably 0.8-3.5V, further preferably 1.2-3.0V, and more preferably 1.8-2.5V; the time of the electrolytic dealloying treatment is 0.5-6h, preferably 2-5.5h, further preferably 3-5h, and more preferably 4-4.5h.

[0078] In the present invention, the electrolysis voltage of the electrolytic dealloying treatment should be lower than the standard electrode potential of the metal element corresponding to the cation in the molten salt but higher than the standard electrode potential of silicon.

[0079] In the present invention, the electrolytic de-alloying treatment needs to be carried out in a protective atmosphere, and the protective atmosphere is preferably nitrogen, argon or helium.

[0080] In the present invention, during the electrolytic dealloying treatment, the auxiliary electrode on the inner wall of the electrolytic container is connected to the negative electrode of the power supply, and the auxiliary electrode at the bottom of the electrolytic container is connected to the positive electrode of the power supply. The potential of the auxiliary electrode of the electrolytic dealloying treatment is 1.5 to 3.0 V, preferably 1.8 to 2.8 V, and more preferably 2.2 to 2.5 V.

[0081] During the electrolytic de-alloying process, the Me element in the Si-Me alloy is effectively removed, the porosity of Si-Me is gradually increased, and silicon remains in a solid state. The potential of the auxiliary electrode is adjusted to be lower than the potential of the working cathode, so that the Me oxidized from the electrolytic Si-Me alloy is x+ Under the action of the electric field force, it moves toward the auxiliary electrode to continuously improve the purity of silicon in the molten salt system. When the electrochemical dealloying process is completed, a porous silicon structure is generated.

[0082] In the present invention, step 3) further comprises the steps of separating the product from the cathode, washing with water, washing with acid and replacing the solvent after the electrolytic de-alloying treatment.

[0083] In the present invention, the pickling is to soak and wash the material with an acid solution, the acid solution includes one or more of nitric acid, hydrochloric acid, sulfuric acid, hydrofluoric acid, phosphoric acid, hydrocyanic acid and perchloric acid, the concentration of the acid solution is 0.1-2 mol / L, preferably 0.5-1.5 mol / L, and more preferably 1-1.2 mol / L; the pickling time is 30-300 min, preferably 50-250 min, more preferably 100-200 min, and more preferably 120-150 min.

[0084] In the present invention, the solvent replacement is to immerse the pickled material in a low-boiling point organic solvent, remove the organic solvent after immersion, and vacuum dry;

[0085] The low boiling point solvent includes one or more of acetone, ether, methanol, ethanol and isopropanol. The soaking time is 30 to 600 min, preferably 120 to 540 min, more preferably 240 to 480 min, and more preferably 300 to 360 min.

[0086] The vacuum drying temperature is 30-60° C., preferably 35-50° C., and more preferably 40-45° C.; the vacuum drying time is 3-10 hours; vacuum drying can reduce the effect of capillary force and avoid the collapse of the porous structure.

[0087] In the present invention, the annealing temperature in step 3) is 300-900°C, preferably 400-850°C, more preferably 500-800°C, and more preferably 600-700°C; the annealing time is 60-300min, preferably 120-270min, more preferably 150-240min, and more preferably 180-210min.

[0088] In the present invention, the annealing needs to be carried out in a protective atmosphere, and the protective atmosphere is preferably nitrogen, argon or helium; the cooling rate of the annealing is 1 to 6°C / min, preferably 1 to 5°C / min, and further preferably 2 to 3°C / min. A slower cooling rate can avoid the generation of internal stress in the material.

[0089] The main purpose of annealing is to repair the structural defects of the material to enhance its stability.

[0090] The present invention also provides a porous nano-silicon negative electrode material prepared by the above preparation method.

[0091] The present invention also provides an application of the porous structure nano silicon negative electrode material in a lithium battery negative electrode material. The specific application method is as follows: the porous structure nano silicon negative electrode material, a conductive agent and a binder are mixed to form a lithium battery negative electrode material.

[0092] In the present invention, the mass ratio of the porous structure nano-silicon negative electrode material, the conductive agent and the binder is 60-80:10-20:10-20, preferably 65-75:12-18:12-18, more preferably 68-72:14-16:14-16, and more preferably 60:15:15.

[0093] The conductive agent includes one or more of graphene, conductive carbon black, carbon nanotubes, polyaniline, acetylene black and polypyrrole.

[0094] The binder includes one or more of polyacrylonitrile, styrene-butadiene rubber, sodium alginate, carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0095] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0096] Example 1

[0097] (1) Assembling the molten salt electrolysis device:

[0098] The anode is a graphite rod with a diameter of 1 cm and a length of 10 cm, the cathode is a molybdenum rod with a diameter of 2 cm and a length of 10 cm, and the electrolysis container is a cylindrical alumina crucible with an inner diameter of 10 cm and a height of 15 cm. The anode graphite rod and the cathode molybdenum rod are fixed in the crucible respectively, ensuring that the distance between the two is 3 cm. The molybdenum mesh auxiliary electrodes are installed on the inner wall and the bottom of the crucible respectively, wherein the molybdenum mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the molybdenum mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The molybdenum mesh on the inner wall and the bottom of the crucible do not contact, and the auxiliary electrode does not contact any electrode during the electrolysis process to avoid short circuit. NaCl and CaCl2 with a molar ratio of 4:6 are mixed to prepare 360 ​​grams of molten salt, and then 10 grams of photovoltaic silicon cutting waste with a particle size between 0.5 and 3 μm are added and mixed thoroughly.

[0099] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0100] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to an alumina crucible, and the molten salt is heated in an argon atmosphere with a flow rate of 20 mL / min, and the heating rate is 3°C / min. When heated to 500°C, it is kept warm for 60 minutes in an argon atmosphere to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation is completed, the temperature is continuously raised to 700°C at a heating rate of 2°C / min. Electrolysis is started after 30 minutes of insulation. For the initial electrolysis, the cathode electrolysis voltage is set to 2.8V, the potential of the auxiliary electrode is set to 3.1V, and the electrolysis time is set to 2h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is carried out, and the minimum value of the high-frequency pulse electrolysis voltage is 3.5V, the maximum value is 4.2V, the duration of each band is 30 seconds, and the potential of the auxiliary electrode is set to 4.3V. During the electrolysis process, silicon-calcium alloy is continuously generated on the cathode surface, and Si-Ca alloy is obtained after 3h.

[0101] (3) Alloy homogenization treatment:

[0102] After the high-frequency pulse electrolysis is completed, the cathode with the electrolysis product attached is lifted from the molten salt and suspended in an argon atmosphere, and the flow rate is adjusted to 30 mL / min. According to the phase transition temperature of the Si-Ca alloy, a staged dynamic temperature control method is adopted to promote the uniform growth of the alloy phase. In the first stage, the temperature is raised from the electrolysis temperature to 800°C at a heating rate of 1.5°C / min and maintained for 30 minutes to promote the initial homogenization of different phases; in the second stage, the temperature is further raised to 950°C and maintained for 40 minutes to homogenize the target phase at a heating rate of 1°C / min. A smaller heating rate helps to inhibit the abnormal growth of grains; in the third stage, the temperature is cooled to 850°C at a cooling rate of 1°C / min to avoid the formation of new phases or the generation of microcracks caused by thermal stress, ensuring that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0103] (4) Dealloying and post-treatment:

[0104] At 850°C in the third stage of alloy homogenization, the cathode of the Si-Ca alloy material is placed back in the molten salt for selective oxidation in an argon atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of calcium in the Si-Ca alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 2.0V, and the electrolysis de-alloying time is 3h. As the calcium metal in the Si-Ca alloy is effectively removed, the porosity of Si-Ca gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.5V, so that the calcium ions oxidized by the electrolytic Si-Ca alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical de-alloying process is completed, a porous silicon structure is generated. After the dealloying is completed, the cathode with porous silicon attached is continuously taken out of the molten salt and suspended in an argon atmosphere to be cooled to room temperature, wherein the cooling rate is 2°C / min; then the electrolysis product is separated from the molybdenum rod and washed with water and pickled with an acid pickling agent of a mixed acid of HCI and HF, and the concentration of the pickling agent is 0.5 mol / L; the pickled product is immersed in ethanol instead of water for 120 min, after the immersion is completed, the organic solvent is removed, and the product is vacuum dried at 45°C for 4 h; after drying, the electrolysis product is placed in a nitrogen atmosphere for annealing heat treatment, the nitrogen flow rate is 25 mL / min, the annealing temperature is 600°C, and the annealing time is 180 min. After the annealing is completed, a porous structure nano-silicon negative electrode material with high hardness is obtained.

[0105] The electrolysis device of this embodiment is as follows Figure 1 As shown, 1-electrolysis container, 2-auxiliary electrode, 3-anode, 4-cathode, 5-molten salt and photovoltaic silicon cutting waste, Figure 1 (a) is a schematic diagram of the preliminary electrolysis and high-frequency pulse electrolysis process, wherein the auxiliary electrode disposed on the inner wall of the electrolysis container is connected to the positive electrode of the power supply, and the auxiliary electrode disposed at the bottom of the electrolysis container is connected to the negative electrode of the power supply; Figure 1(b) is a schematic diagram of the dealloying process. The auxiliary electrode arranged on the inner wall of the electrolytic container is connected to the negative electrode of the power supply, and the auxiliary electrode arranged at the bottom of the electrolytic container is connected to the positive electrode of the power supply. During the electrolytic reduction and alloying process, the potential of the auxiliary electrode is higher than the potential of the cathode, so an electric field pointing from high potential to low potential is generated between the auxiliary electrode and the cathode. Therefore, during the electrolysis process, the calcium ions and sodium ions in the molten salt move toward the cathode more easily, thereby improving the electrolysis efficiency. Under the action of the auxiliary electrode, the calcium ions and sodium ions move toward the cathode and are reduced to calcium metal and sodium metal by electrons at the cathode. The calcium metal combines with silicon to form a Si-Ca alloy, while the sodium metal is difficult to form a stable Si-Na alloy at high temperature due to its low melting point and high volatility. The main purpose of adding NaCl during the electrolysis process is to lower the melting point of the mixed molten salt, increase the ionic conductivity and stabilize the molten salt environment. During the electrolytic de-alloying process, the voltage applied to the cathode is higher than the oxidation voltage of silicon at the electrolysis temperature but lower than the oxidation voltage of calcium metal. In addition, the voltage applied to the cathode must also be lower than the voltage of the auxiliary electrode. In this way, after dealloying, the calcium metal in the Si-Ca alloy is oxidized to calcium ions. The calcium ions move toward the auxiliary electrode under the action of the electric field force, thereby promoting the formation of a high-purity porous silicon structure at the cathode.

[0106] The SEM image of photovoltaic silicon cutting waste in this embodiment is shown in Figure 2 It can be seen that photovoltaic silicon cutting waste mainly exists in irregular flake structures, and these particles are evenly distributed without obvious agglomeration. This uniform distribution and flake morphology are conducive to increasing the surface area and reaction interface of the particles, thereby providing higher reaction efficiency and uniform current distribution for the subsequent electrolytic reduction process, and promoting the uniformity and sufficiency of the reaction.

[0107] The pulse potential applied to the cathode during the high-frequency pulse electrolysis alloying process of this embodiment is as follows: Figure 3 As shown, the reduction is carried out at a reduction potential greater than that of calcium ions and sodium ions at the electrolysis temperature. The pulse voltage can dynamically adjust the ion concentration near the electrode surface by alternately applying high and low voltages, effectively slowing down the concentration polarization caused by ion depletion or accumulation, thereby improving the continuity and stability of the electrolysis reaction. At the same time, the dynamic change of the pulse voltage continuously changes the energy state of the electrode surface, which helps to destroy the passivation layer or reduce the deposition of side reaction products, further optimizing the electrochemical environment.

[0108] The SEM image of the nanoporous silicon negative electrode obtained by molten salt electrolysis dealloying and post-treatment in this embodiment is as follows: Figure 4 As shown. Figure 4 It can be seen that a highly developed porous structure with uniform pore size distribution has been formed on the surface of silicon waste, and the specific surface area has increased significantly. Figure 2 and Figure 4It can be clearly seen that the method of this embodiment successfully converts sheet-like photovoltaic silicon cutting waste into nanoporous silicon structure on a large scale.

[0109] The XRD patterns of the alloying product and the electrolytic de-alloying product of this embodiment are shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the alloyed product after dynamic temperature control treatment is mainly composed of CaSi phase, and no peaks of other impurity phases appear, indicating that in the alloying process, the formation of unnecessary phases is successfully suppressed through precise temperature control, and a pure CaSi phase is obtained. After the alloyed product is subsequently subjected to electrolytic de-alloying treatment, the XRD spectrum shows that the characteristic peaks originally belonging to the CaSi phase almost completely disappear, and only the characteristic peaks of the Si phase are retained. This shows that the electrolytic de-alloying process effectively removes the calcium element in the alloy and successfully converts it into a pure silicon phase material. This result proves the efficiency and selectivity of the electrolytic de-alloying method, and provides a strong basis for the preparation of high-purity nanoporous silicon materials.

[0110] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The cycle performance of the lithium battery silicon negative electrode is as follows: Figure 6 As shown, the first discharge specific capacity of the lithium battery silicon negative electrode is 2964.6 mAh / g, the first coulomb efficiency can reach 84.9%, and the reversible specific capacity after 200 cycles is 1200.3 mAh / g.

[0111] Example 2

[0112] (1) Assembling the molten salt electrolysis device:

[0113] The anode is a graphite rod with a diameter of 1.5 cm and a length of 12 cm, the cathode is a platinum rod with a diameter of 2.5 cm and a length of 12 cm, and the electrolysis container is a cylindrical alumina crucible with an inner diameter of 15 cm and a height of 18 cm. The anode graphite rod and the cathode platinum rod are fixed in the crucible respectively, ensuring that the distance between the two is 3.5 cm. The platinum mesh auxiliary electrode is installed on the inner wall and the bottom of the crucible respectively, wherein the platinum mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the platinum mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The platinum mesh on the inner wall and the bottom of the crucible do not touch each other, and the auxiliary electrode does not touch any electrode during the electrolysis process to avoid short circuit. NaCl and MgCl with a molar ratio of 5:5 are added. 2 Mix and prepare 380 grams of molten salt, then add 8 grams of photovoltaic silicon cutting waste with a particle size of 1 to 4 μm and mix thoroughly.

[0114] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0115] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to a zirconia crucible, and the molten salt is heated in a nitrogen atmosphere with a flow rate of 25 mL / min, and the heating rate is 2.5°C / min. When heated to 400°C, it is kept warm for 80 minutes in a nitrogen atmosphere to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation, the temperature is continuously raised to 750°C at a heating rate of 2.5°C / min. After being kept warm for 20 minutes, electrolysis is started. For the initial electrolysis, the cathode electrolysis voltage is set to 2.4V, the potential of the auxiliary electrode is set to 3.1V, and the electrolysis time is 2.5h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is carried out, and the minimum value of the high-frequency pulse electrolysis voltage is 2.8V, the maximum value is 3.3V, the duration of each band is 40 seconds, and the potential of the auxiliary electrode is set to 3.5V. During the electrolysis process, silicon-magnesium alloy is continuously generated on the cathode surface, and Si-Mg alloy is obtained after 2.5 hours.

[0116] (3) Alloy homogenization treatment:

[0117] After the high-frequency pulse electrolysis, the cathode with the electrolysis product attached was lifted from the molten salt and suspended in a nitrogen atmosphere, and the flow rate was adjusted to 25 mL / min. According to the phase transition temperature of Si-Mg alloy, a staged dynamic temperature control method was adopted to promote the uniform growth of the alloy phase. In the first stage, the temperature was raised from the electrolysis temperature to 800°C at a heating rate of 1°C / min and maintained for 40 minutes to promote the initial homogenization of different phases; in the second stage, the temperature was further raised to 900°C and maintained for 30 minutes to homogenize the target phase at a heating rate of 1.5°C / min. A smaller heating rate helps to inhibit the abnormal growth of grains; in the third stage, the temperature was lowered to 700°C at a cooling rate of 1.5°C / min to avoid the formation of new phases or the generation of microcracks caused by thermal stress, ensuring that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0118] (4) Dealloying and post-treatment:

[0119] At 700°C in the third stage of alloy homogenization, the cathode with Si-Mg alloy material is placed back in the molten salt for selective oxidation in a nitrogen atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of magnesium in Si-Mg alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 1.9V, and the electrolysis de-alloying time is 2.5h. As the magnesium metal in the Si-Mg alloy is effectively removed, the porosity of Si-Mg gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.4V, so that the magnesium ions oxidized by the electrolysis of Si-Mg alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical de-alloying process is completed, a porous silicon structure is generated. After the dealloying is completed, the cathode with porous silicon attached is taken out of the molten salt and suspended in a nitrogen atmosphere to cool to room temperature, with a cooling rate of 1.5°C / min. Then, the electrolysis product is separated from the platinum rod and washed with water and acid. The acid washing reagent used is H 2 SO 4 A mixed acid of H 2 SO 4 and HF concentrations are both 0.3 mol / L; the pickled product is immersed in acetone instead of water for 150 min. After the soaking, the organic solvent is removed and vacuum dried at 50°C for 5 h. After drying, the electrolysis product is placed in a nitrogen atmosphere for annealing heat treatment. The nitrogen flow rate is 20 mL / min, the annealing temperature is 650°C, and the annealing time is 210 min. After the annealing, a high-hardness porous structure nano-silicon negative electrode material is obtained.

[0120] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode is 3123.8 mAh / g, the first coulomb efficiency can reach 85.7%, and the reversible specific capacity after 200 cycles is 1372.3 mAh / g.

[0121] Example 3

[0122] (1) Assembling the molten salt electrolysis device:

[0123] The anode is a glassy carbon rod with a diameter of 2.0 cm and a length of 15 cm, the cathode is a tungsten rod with a diameter of 3.0 cm and a length of 15 cm, and the electrolysis container is a cylindrical boron nitride crucible with an inner diameter of 20 cm and a height of 25 cm. The anode glassy carbon rod and the cathode tungsten rod are fixed in the crucible respectively, ensuring that the distance between the two is 4 cm. The tungsten mesh auxiliary electrode is installed on the inner wall and bottom of the crucible respectively, wherein the tungsten mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the tungsten mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The tungsten mesh on the inner wall and the bottom of the crucible do not touch each other, and the auxiliary electrode does not touch any electrode during the electrolysis process to avoid short circuit. NaCl and AlCl with a molar ratio of 6:4 are added. 3 Mix and prepare 500 grams of molten salt, then add 12 grams of photovoltaic silicon cutting waste with a particle size of 0.5 to 5 μm, and mix thoroughly.

[0124] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0125] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to a boron nitride crucible, and the molten salt is heated in a helium atmosphere with a flow rate of 25 mL / min, and the heating rate is 2.0°C / min. When heated to 600°C, it is kept in a helium atmosphere for 50 minutes to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation is completed, the temperature is continuously raised to 800°C, and the heating rate is 1.5°C / min. After the insulation is completed, electrolysis is started after 25 minutes. For the initial electrolysis, the cathode electrolysis voltage is set to 1.9V, the potential of the auxiliary electrode is set to 2.2V, and the electrolysis time is 3h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is carried out, and the minimum value of the high-frequency pulse electrolysis voltage is 2.0V, the maximum value is 2.8V, the duration of each band is 35 seconds, and the potential of the auxiliary electrode is set to 3.0V. During the electrolysis process, silicon-aluminum alloy is continuously generated on the cathode surface, and Si-Al alloy is obtained after 2h.

[0126] (3) Alloy homogenization treatment:

[0127] After the high-frequency pulse electrolysis, the cathode with the electrolysis product attached was lifted from the molten salt and suspended in the helium atmosphere, and the flow rate was adjusted to 35 mL / min. According to the phase transition temperature of Si-Al alloy, a staged dynamic temperature control method was adopted to promote the uniform growth of the alloy phase. In the first stage, the temperature was raised from the electrolysis temperature to 850°C at a heating rate of 2°C / min and maintained for 40 minutes to promote the initial homogenization of different phases; in the second stage, the temperature was further raised to 950°C and kept for 50 minutes to homogenize the target phase at a heating rate of 2°C / min. A smaller heating rate helps to inhibit the abnormal growth of grains; in the third stage, the temperature was lowered to 800°C at a cooling rate of 1.5°C / min to avoid the formation of new phases or the generation of microcracks caused by thermal stress, ensuring that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0128] (4) Dealloying and post-treatment:

[0129] At 800°C in the third stage of alloy homogenization, the cathode with Si-Al alloy material attached is placed back in the molten salt for selective oxidation in a helium atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of aluminum element in Si-Al alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 1.7V, and the electrolysis de-alloying time is 2h. As the aluminum metal in the Si-Al alloy is effectively removed, the porosity of Si-Al gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.2V, so that the aluminum ions oxidized by the electrolytic Si-Al alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical de-alloying process is completed, a porous silicon structure is generated. After the dealloying is completed, the cathode with porous silicon attached is continuously taken out of the molten salt and suspended in a helium atmosphere to be cooled to room temperature, wherein the cooling rate is 2°C / min; then the electrolysis product is separated from the tungsten rod and washed with water and pickled with HCl, and the concentration of the pickling agent is 0.2 mol / L; the pickled product is immersed in methanol instead of water for 180 min, after the immersion is completed, the organic solvent is removed, and vacuum dried at a temperature of 40°C for 6 h; after drying, the electrolysis product is placed in a helium atmosphere for annealing heat treatment, the helium flow rate is 30 mL / min, the annealing temperature is 700°C, and the annealing time is 200 min. After the annealing is completed, a porous structure nano-silicon negative electrode with high hardness is obtained.

[0130] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode is 3086.9 mAh / g, the first coulomb efficiency can reach 83.7%, and the reversible specific capacity after 200 cycles is 1228.6 mAh / g.

[0131] Example 4

[0132] (1) Assembling the molten salt electrolysis device:

[0133] The anode is an extruded carbon rod with a diameter of 1 cm and a length of 15 cm, the cathode is a zirconium rod with a diameter of 1.5 cm and a length of 15 cm, and the electrolysis container is a cylindrical magnesium oxide crucible with an inner diameter of 13 cm and a height of 20 cm. The anode extruded carbon rod and the cathode zirconium rod are fixed in the crucible respectively, ensuring that the distance between the two is 2.5 cm. The zirconium mesh auxiliary electrode is installed on the inner wall and the bottom of the crucible respectively, wherein the zirconium mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the zirconium mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The zirconium mesh on the inner wall and the bottom of the crucible do not touch each other, and the auxiliary electrode does not touch any electrode during the electrolysis process to avoid short circuit. NaCl and CuF with a molar ratio of 7:3 are added. 2 Mix and prepare 450 grams of molten salt, then add 8 grams of photovoltaic silicon cutting waste with a particle size of 1 to 6 μm and mix thoroughly.

[0134] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0135] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to a magnesium oxide crucible, and the molten salt is heated in an argon atmosphere with a flow rate of 30 mL / min, and the heating rate is 3°C / min. When heated to 600°C, it is kept in an argon atmosphere for 80 minutes to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation, the temperature is continuously raised to 850°C at a heating rate of 2.0°C / min. Electrolysis is started after 35 minutes of insulation. For the initial electrolysis, the cathode electrolysis voltage is set to 1.8V, the potential of the auxiliary electrode is set to 2.3V, and the electrolysis time is 2h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is performed, and the minimum value of the high-frequency pulse electrolysis voltage is 2.2V, the maximum value is 2.8V, the duration of each band is 45 seconds, and the potential of the auxiliary electrode is set to 3.1V. During the electrolysis process, silicon-copper alloy is continuously generated on the cathode surface, and Si-Cu alloy is obtained after 3h.

[0136] (3) Alloy homogenization treatment:

[0137] After the high-frequency pulse electrolysis, the cathode with the electrolysis product attached was lifted from the molten salt and suspended in an argon atmosphere, and the flow rate was adjusted to 20 mL / min. According to the phase transition temperature of the Si-Cu alloy, a staged dynamic temperature control method was adopted to promote the uniform growth of the alloy phase. In the first stage, the temperature was raised from the electrolysis temperature to 900 ° C, the heating rate was 1.5 ° C / min, and maintained for 35 minutes to promote the initial homogenization of different phases; in the second stage, the temperature was further raised to 980 ° C, and then kept for 35 minutes to homogenize the target phase, the heating rate was 1 ° C / min, and a smaller heating rate was helpful to inhibit the abnormal growth of grains; in the third stage, the temperature was cooled to 820 ° C, and the cooling rate was 2 ° C / min to avoid the formation of new phases or the generation of microcracks caused by thermal stress, so as to ensure that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0138] (4) Dealloying and post-treatment:

[0139] At 820°C in the third stage of alloy homogenization, the cathode attached to the Si-Cu alloy material is placed back in the molten salt for selective oxidation in an argon atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of the copper element in the Si-Cu alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 1.8V, and the electrolysis de-alloying time is 3h. As the copper metal in the Si-Cu alloy is effectively removed, the porosity of Si-Cu gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.3V, so that the copper ions oxidized by the electrolysis of the Si-Cu alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical de-alloying process is completed, a porous silicon structure is generated. After the de-alloying is completed, the cathode attached to the porous silicon is continuously taken out of the molten salt and suspended in an argon atmosphere to cool to room temperature, wherein the cooling rate is 2.5°C / min; then the electrolysis product is separated from the zirconium rod and washed with water and acid, and the acid washing reagent used is H 2 SO 4 and HCl mixed acid, the concentration of the pickling reagent is 0.2mol / L; the pickling product is immersed in ether instead of water for 210min, after the soaking, the organic solvent is removed, and vacuum dried at 45°C for 5.5h; after drying, the electrolysis product is placed in a nitrogen atmosphere for annealing heat treatment, the nitrogen flow rate is 30mL / min, the annealing temperature is 730°C, the annealing time is 150min, and after the annealing, a high-hardness porous structure nano-silicon negative electrode is obtained.

[0140] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode is 2847.6 mAh / g, the first coulomb efficiency can reach 82.3%, and the reversible specific capacity after 200 cycles is 1091.8 mAh / g.

[0141] Example 5

[0142] (1) Assembling the molten salt electrolysis device:

[0143] The anode is a carbon fiber rod with a diameter of 2 cm and a length of 10 cm, the cathode is a platinum rod with a diameter of 3.5 cm and a length of 10 cm, and the electrolysis container is a cylindrical graphite crucible with an inner diameter of 15 cm and a height of 15 cm. The anode carbon fiber rod and the cathode platinum rod are fixed in the crucible respectively, ensuring that the distance between the two is 3 cm. The tungsten mesh auxiliary electrode is installed on the inner wall and bottom of the crucible respectively, wherein the tungsten mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the tungsten mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The tungsten mesh on the inner wall and the bottom of the crucible do not touch each other, and the auxiliary electrode does not touch any electrode during the electrolysis process to avoid short circuit. KCl and FeF with a molar ratio of 6:4 are added. 2 Mix and prepare 500 grams of molten salt, then add 14 grams of photovoltaic silicon cutting waste with a particle size of 0.5 to 7 μm, and mix thoroughly.

[0144] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0145] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to a graphite crucible, and the molten salt is heated in a helium atmosphere with a flow rate of 30 mL / min, and the heating rate is 4°C / min. When heated to 550°C, it is kept warm for 40 minutes in a helium atmosphere to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation, the temperature is continuously raised to 820°C at a heating rate of 3°C / min. After the insulation is completed, electrolysis is started after 30 minutes. For the initial electrolysis, the cathode electrolysis voltage is set to 2.6V, the potential of the auxiliary electrode is set to 3V, and the electrolysis time is 1h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is carried out, and the minimum value of the high-frequency pulse electrolysis voltage is 3.1V, the maximum value is 4.1V, the duration of each band is 50 seconds, and the potential of the auxiliary electrode is set to 4.2V. During the electrolysis process, ferrosilicon alloy is continuously generated on the cathode surface, and Si-Fe alloy is obtained after 3.5 hours of pulse electrolysis.

[0146] (3) Alloy homogenization treatment:

[0147] After the high-frequency pulse electrolysis is completed, the cathode with the electrolysis product attached is lifted from the molten salt and suspended in the helium atmosphere, and the flow rate is adjusted to 35mL / min. According to the phase transition temperature of Si-Fe alloy, a staged dynamic temperature control method is adopted to promote the uniform growth of alloy phase. In the first stage, the temperature is raised from the electrolysis temperature to 950℃, the heating rate is 2℃ / min, and it is kept for 50min to promote the initial homogenization of different phases; in the second stage, the temperature is further raised to 1050℃ and kept for 35min to homogenize the target phase, the heating rate is 2℃ / min, and the smaller heating rate helps to inhibit the abnormal growth of grains; in the third stage, the temperature is lowered to 780℃, the cooling rate is 2℃ / min, to avoid the formation of new phases or the generation of microcracks caused by thermal stress, and to ensure that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0148] (4) Dealloying and post-treatment:

[0149] At 780°C in the third stage of alloy homogenization, the cathode with Si-Fe alloy material attached is placed back in the molten salt for selective oxidation in a helium atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of iron in Si-Fe alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 2.3V, and the electrolysis dealloying time is 3.5h. As the iron metal in the Si-Fe alloy is effectively removed, the porosity of Si-Fe gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.8V, so that the iron ions oxidized by the electrolytic Si-Fe alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical dealloying process is completed, a porous silicon structure is generated. After the dealloying is completed, the cathode with porous silicon attached is continuously taken out of the molten salt and suspended in a helium atmosphere to be cooled to room temperature, wherein the cooling rate is 1.5°C / min; then the electrolysis product is separated from the platinum rod and washed with water and pickled with an acid washing agent of a mixed acid of HCl and HF, and the concentration of the pickling agent is 0.4 mol / L; the pickled product is immersed in isopropanol instead of water for 180 min, after the immersion is completed, the organic solvent is removed, and the product is vacuum dried at a temperature of 55°C for 6.5 h; after drying, the electrolysis product is placed in an argon atmosphere for annealing heat treatment, the argon flow rate is 25 mL / min, the annealing temperature is 600°C, and the annealing time is 240 min. After the annealing is completed, a porous structure nano-silicon negative electrode with high hardness is obtained.

[0150] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode is 2837.6 mAh / g, the first coulomb efficiency can reach 83.8%, and the reversible specific capacity after 200 cycles is 1139.8 mAh / g.

[0151] Example 6

[0152] (1) Assembling the molten salt electrolysis device:

[0153] The anode is an impregnated carbon rod with a diameter of 2.5 cm and a length of 10 cm, the cathode is a molybdenum rod with a diameter of 2.5 cm and a length of 10 cm, and the electrolysis container is a cylindrical magnesium oxide crucible with an inner diameter of 15 cm and a height of 18 cm. The anode impregnated carbon rod and the cathode molybdenum rod are fixed in the crucible respectively, ensuring that the distance between the two is 3 cm. The nickel mesh auxiliary electrode is installed on the inner wall and the bottom of the crucible respectively, wherein the nickel mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the nickel mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The nickel mesh on the inner wall and the bottom of the crucible do not touch each other, and the auxiliary electrode does not touch any electrode during the electrolysis process to avoid short circuit. LiI and BaCl with a molar ratio of 5:5 are added. 2 Mix and prepare 480 grams of molten salt, then add 10 grams of photovoltaic silicon cutting waste with a particle size of 2 to 7 μm, and mix thoroughly.

[0154] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0155] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to a magnesium oxide crucible, and the molten salt is heated in a nitrogen atmosphere with a flow rate of 35 mL / min, and the heating rate is 3°C / min. When heated to 450°C, it is kept warm for 60 minutes in a nitrogen atmosphere to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation, the temperature is continuously raised to 680°C at a heating rate of 2°C / min. After the insulation is completed, the electrolysis is started after 40 minutes. The cathode electrolysis voltage is set to 2.4V for the initial electrolysis, the potential of the auxiliary electrode is set to 2.8V, and the electrolysis time is 1.5h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is carried out, and the minimum value of the high-frequency pulse electrolysis voltage is 3.8V, the maximum value is 4.2V, the duration of each band is 25 seconds, and the potential of the auxiliary electrode is set to 4.3V. During the electrolysis process, silicon-lithium alloy is continuously generated on the cathode surface, and Si-Li alloy is obtained after 3 hours of pulse electrolysis.

[0156] (3) Alloy homogenization treatment:

[0157] After the high-frequency pulse electrolysis, the cathode with the electrolysis product attached was lifted from the molten salt and suspended in a nitrogen atmosphere, and the flow rate was adjusted to 20 mL / min. According to the phase transition temperature of the Si-Li alloy, a staged dynamic temperature control method was adopted to promote the uniform growth of the alloy phase. In the first stage, the temperature was raised from the electrolysis temperature to 750°C at a heating rate of 1.5°C / min and maintained for 30 minutes to promote the initial homogenization of different phases; in the second stage, the temperature was further raised to 800°C and maintained for 20 minutes to homogenize the target phase at a heating rate of 2°C / min. A smaller heating rate helps to inhibit the abnormal growth of grains; in the third stage, the temperature was cooled to 650°C at a cooling rate of 2°C / min to avoid the formation of new phases or the generation of microcracks caused by thermal stress, ensuring that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0158] (4) Dealloying and post-treatment:

[0159] At 650°C in the third stage of alloy homogenization, the cathode with Si-Mg alloy material attached is placed back in the molten salt for selective oxidation in a nitrogen atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of lithium element in Si-Li alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 2.1V, and the electrolysis de-alloying time is 3h. As the lithium metal in the Si-Li alloy is effectively removed, the porosity of Si-Li gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.5V, so that the lithium ions oxidized by the electrolysis of Si-Li alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical de-alloying process is completed, a porous silicon structure is generated. After the dealloying is completed, the cathode with porous silicon attached is continuously taken out of the molten salt and suspended in a nitrogen atmosphere to be cooled to room temperature, wherein the cooling rate is 3°C / min; then the electrolysis product is separated from the molybdenum rod and washed with water and pickled with HF at a concentration of 0.5 mol / L; the pickled product is immersed in methanol instead of water for 200 min, after the immersion is completed, the organic solvent is removed, and vacuum dried at a temperature of 50°C for 6 h; after drying, the electrolysis product is placed in a helium atmosphere for annealing heat treatment, the helium flow rate is 30 mL / min, the annealing temperature is 630°C, and the annealing time is 180 min. After the annealing is completed, a porous structure nano-silicon negative electrode with high hardness is obtained.

[0160] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode is 3201.3 mAh / g, the first coulombic efficiency can reach 82.5%, and the reversible specific capacity after 200 cycles is 1187.2 mAh / g.

[0161] Example 7

[0162] (1) Assembling the molten salt electrolysis device:

[0163] The anode is a graphitized carbon rod with a diameter of 2.5 cm and a length of 15 cm, the cathode is a zirconium rod with a diameter of 3 cm and a length of 15 cm, and the electrolysis container is a cylindrical alumina crucible with an inner diameter of 13 cm and a height of 20 cm. The anode graphitized carbon rod and the cathode zirconium rod are fixed in the crucible respectively, ensuring that the distance between the two is 3.5 cm. The titanium mesh auxiliary electrode is installed on the inner wall and the bottom of the crucible respectively, wherein the platinum mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the titanium mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The titanium mesh on the inner wall and the bottom of the crucible do not touch each other, and the auxiliary electrode does not touch any electrode during the electrolysis process to avoid short circuit. NaBr and MnF with a molar ratio of 4:6 are added. 2 Mix and prepare 550 grams of molten salt, then add 14 grams of photovoltaic silicon cutting waste with a particle size of 0.5 to 8 μm, and mix thoroughly.

[0164] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0165] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to an alumina crucible, and the molten salt is heated in an argon atmosphere with a flow rate of 20 mL / min, and the heating rate is 4°C / min. When heated to 600°C, it is kept warm for 50 minutes in an argon atmosphere to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation is completed, the temperature is continuously raised to 850°C at a heating rate of 3°C / min. Electrolysis is started after 30 minutes of insulation. For the initial electrolysis, the cathode electrolysis voltage is set to 2.8V, the potential of the auxiliary electrode is set to 3.2V, and the electrolysis time is 2h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is carried out, and the minimum value of the high-frequency pulse electrolysis voltage is 3.5V, the maximum value is 4.3V, the duration of each band is 30 seconds, and the potential of the auxiliary electrode is set to 4.5V. During the electrolysis process, silicon-manganese alloy is continuously generated on the cathode surface, and Si-Mn alloy is obtained after 3.5 hours of pulse electrolysis.

[0166] (3) Alloy homogenization treatment:

[0167] After the high-frequency pulse electrolysis, the cathode with the electrolysis product attached was lifted from the molten salt and suspended in an argon atmosphere, and the flow rate was adjusted to 30 mL / min. According to the phase transition temperature of the Si-Mn alloy, a staged dynamic temperature control method was adopted to promote the uniform growth of the alloy phase. In the first stage, the temperature was raised from the electrolysis temperature to 950°C at a heating rate of 2°C / min and maintained for 45 minutes to promote the initial homogenization of different phases; in the second stage, the temperature was further raised to 1100°C and then kept for 35 minutes to homogenize the target phase at a heating rate of 2.5°C / min. A smaller heating rate helps to inhibit the abnormal growth of grains; in the third stage, the temperature was lowered to 730°C at a cooling rate of 2.5°C / min to avoid the formation of new phases or the generation of microcracks caused by thermal stress, ensuring that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0168] (4) Dealloying and post-treatment:

[0169] At 730°C in the third stage of alloy homogenization, the cathode with Si-Mn alloy material attached is placed back in the molten salt for selective oxidation in an argon atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of manganese in Si-Mn alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 2.0V, and the electrolysis de-alloying time is 4h. As the manganese metal in the Si-Mn alloy is effectively removed, the porosity of Si-Mn gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.5V, so that the manganese ions oxidized by the electrolysis of Si-Mn alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical de-alloying process is completed, a porous silicon structure is generated. After the dealloying is completed, the cathode with porous silicon attached is taken out of the molten salt and suspended in an argon atmosphere to cool to room temperature, with a cooling rate of 2°C / min. Then, the electrolysis product is separated from the zirconium rod and washed with water and acid. The acid washing reagent used is H 2 SO 4 and HF mixed acid, the concentration of the pickling reagent is 0.5 mol / L; the pickling product is immersed in ethanol instead of water for 240 minutes. After the soaking, the organic solvent is removed and vacuum dried at 45°C for 7 hours; after drying, the electrolysis product is placed in a nitrogen atmosphere for annealing heat treatment, the nitrogen flow rate is 35 mL / min, the annealing temperature is 680°C, the annealing time is 200 minutes, and a high-hardness porous structure nano-silicon negative electrode is obtained after annealing.

[0170] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode is 2873.4 mAh / g, the first coulombic efficiency can reach 82.3%, and the reversible specific capacity after 200 cycles is 1086.7 mAh / g.

[0171] Example 8

[0172] (1) Assembling the molten salt electrolysis device:

[0173] The anode is a high-purity carbon rod with a diameter of 2.0 cm and a length of 10 cm, the cathode is a platinum rod with a diameter of 4 cm and a length of 10 cm, and the electrolysis container is a cylindrical boron nitride crucible with an inner diameter of 13 cm and a height of 15 cm. The anode high-purity carbon rod and the cathode tungsten rod are fixed in the crucible respectively, ensuring that the distance between the two is 4 cm. The tantalum mesh auxiliary electrode is installed on the inner wall and the bottom of the crucible respectively, wherein the tantalum mesh on the inner wall of the crucible is connected to the positive electrode of the power supply, and the tantalum mesh at the bottom of the crucible is connected to the negative electrode of the power supply. The tantalum mesh on the inner wall and the bottom of the crucible do not touch each other, and the auxiliary electrode does not touch any electrode during the electrolysis process to avoid short circuit. NaI and NiF with a molar ratio of 5:5 are added. 2 Mix and prepare 520 grams of molten salt, then add 10 grams of photovoltaic silicon cutting waste with a particle size of 2 to 8.5 μm, and mix thoroughly.

[0174] (2) Initial electrolysis and high-frequency pulse potential electrolysis:

[0175] The uniformly mixed molten salt and photovoltaic silicon cutting waste are added to a boron nitride crucible, and the molten salt is heated in a nitrogen atmosphere with a flow rate of 35 mL / min, and the heating rate is 4.5°C / min. When heated to 500°C, it is kept warm for 60 minutes in a nitrogen atmosphere to fully remove the moisture in the molten salt and avoid the occurrence of side reactions caused by the moisture in the molten salt during electrolysis. After the insulation is completed, the temperature is continuously raised to 800°C at a heating rate of 3.5°C / min. After the insulation is completed, electrolysis is started after 35 minutes. The cathode electrolysis voltage is set to 2.5V for the initial electrolysis, the potential of the auxiliary electrode is set to 2.9V, and the electrolysis time is 1.5h to fully remove impurities and oxide layers in the molten salt; then high-frequency pulse electrolysis is carried out, and the minimum value of the high-frequency pulse electrolysis voltage is 2.8V, the maximum value is 3.6V, the duration of each band is 40 seconds, and the potential of the auxiliary electrode is set to 3.8V. During the electrolysis process, silicon-nickel alloy is continuously generated on the cathode surface, and Si-Ni alloy is obtained after 4 hours of pulse electrolysis.

[0176] (3) Alloy homogenization treatment:

[0177] After the high-frequency pulse electrolysis, the cathode with the electrolysis product attached was lifted from the molten salt and suspended in a nitrogen atmosphere, and the flow rate was adjusted to 40 mL / min. According to the phase transition temperature of the Si-Ni alloy, a staged dynamic temperature control method was adopted to promote the uniform growth of the alloy phase. In the first stage, the temperature was raised from the electrolysis temperature to 880°C at a heating rate of 1.5°C / min and maintained for 40 minutes to promote the initial homogenization of different phases; in the second stage, the temperature was further raised to 950°C and kept for 30 minutes to homogenize the target phase at a heating rate of 1°C / min. A smaller heating rate helps to inhibit the abnormal growth of grains; in the third stage, the temperature was lowered to 850°C at a cooling rate of 2°C / min to avoid the formation of new phases or the generation of microcracks caused by thermal stress, ensuring that the alloy has the stable phase and microstructure required for the subsequent dealloying process.

[0178] (4) Dealloying and post-treatment:

[0179] At 850°C in the third stage of alloy homogenization, the cathode with Si-Ni alloy material is placed back in the molten salt for selective oxidation in a nitrogen atmosphere. The electrolysis voltage applied in this step should be lower than the standard electrode potential of nickel element in Si-Ni alloy at the electrolysis temperature, but higher than the standard electrode potential of silicon. The specific voltage is set to 2.2V, and the electrolysis de-alloying time is 3.5h. As the nickel metal in the Si-Ni alloy is effectively removed, the porosity of Si-Ni gradually increases, and silicon remains in a solid state. In addition, the potential of the auxiliary electrode is set to 1.6V, so that the nickel ions oxidized by the electrolytic Si-Ni alloy move toward the auxiliary electrode under the action of the electric field force, so as to continuously improve the purity of silicon in the molten salt system. When the electrochemical de-alloying process is completed, a porous silicon structure is generated. After the dealloying is completed, the cathode with porous silicon attached is continuously taken out of the molten salt and suspended in a nitrogen atmosphere to be cooled to room temperature, wherein the cooling rate is 3°C / min; then the electrolytic product is separated from the tungsten rod and washed with water and pickled with an acid washing agent of a mixed acid of HNO3 and HF, and the concentration of the pickling agent is 0.2 mol / L; the pickled product is immersed in ether instead of water for 270 min, after the immersion is completed, the organic solvent is removed, and the product is vacuum dried at 50°C for 7.5 h; after drying, the electrolytic product is placed in an argon atmosphere for annealing heat treatment, the argon flow rate is 40 mL / min, the annealing temperature is 800°C, and the annealing time is 150 min. After the annealing is completed, a porous structure nano-silicon negative electrode with high hardness is obtained.

[0180] The porous structure nano-silicon negative electrode material prepared in this embodiment is used as the lithium battery silicon negative electrode material to test its electrochemical performance. The test method is carried out in accordance with the method in Appendix D of the national standard GB / T 38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode is 2916.7 mAh / g, the first coulomb efficiency can reach 84.2%, and the reversible specific capacity after 200 cycles is 1108.2 mAh / g.

[0181] Comparative Example 1

[0182] The photovoltaic silicon cutting waste (particle size of 0.5-3 μm) described in Example 1 is directly used as a raw material to prepare the lithium battery silicon negative electrode material: the photovoltaic silicon cutting waste is first heated in an argon atmosphere with a flow rate of 20 mL / min, and the heating rate is 3°C / min. When it is heated to 500°C, it is kept in an argon atmosphere for 60 minutes to fully remove the moisture in the photovoltaic silicon cutting waste. The comparative material test method is carried out according to the method in Appendix D of the national standard GB / T38823-2020. The cycle performance of the lithium battery silicon negative electrode material is as follows Figure 6 As shown, the first discharge specific capacity of the lithium battery silicon negative electrode material in this comparative example is 2538.9 mAh / g, the first coulombic efficiency can reach 78.6%, and the reversible specific capacity after 200 cycles is 492.8 mAh / g; and the reversible specific capacity of Example 1 after 200 cycles is 707.5 mAh / g higher than that of the comparative example, so the long cycle performance of Example 1 is much greater than the long cycle performance of photovoltaic silicon cutting waste (sheet).

[0183] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous nano-silicon negative electrode material, characterized in that: The following steps are involved: 1) Mixing photovoltaic silicon cutting waste with molten salt, and sequentially performing primary electrolysis and high-frequency pulse electrolysis in an electrolysis container provided with an auxiliary electrode to obtain Si-Me alloy; 2) performing alloy homogenization treatment on Si-Me alloy; 3) placing the Si-Me alloy after the alloy homogenization treatment in an electrolytic container again for electrolytic dealloying treatment, and then annealing to obtain a porous structure nano-silicon negative electrode material; The auxiliary electrodes are arranged on the inner wall and the bottom of the electrolysis container, and the auxiliary electrodes on the inner wall and the bottom are not in contact.

2. The method for preparing a porous structure nano-silicon negative electrode material according to claim 1, characterized in that: The auxiliary electrode is made of one or more of molybdenum, titanium, platinum, tungsten, tantalum, zirconium or nickel metal materials; The anodes of the primary electrolysis, high-frequency pulse electrolysis and electrolytic dealloying treatment are independently made of carbon materials, and the cathodes are independently made of molybdenum, platinum, tungsten or zirconium materials.

3. The method for preparing a porous structure nano-silicon negative electrode material according to claim 2, characterized in that: The particle size of the photovoltaic silicon cutting waste in step 1) is 0.5 to 10 μm; The molten salt is a metal halide; The mass ratio of the photovoltaic silicon cutting waste to the molten salt is 1-20:100-500.

4. The method for preparing a porous nano-silicon negative electrode material according to claim 3, characterized in that: The temperature of the initial electrolysis in step 1) is 500-1200° C.; The voltage of the initial electrolysis is greater than the theoretical decomposition voltage of the oxide corresponding to the cation in the molten salt at the electrolysis temperature and less than the minimum electrolysis voltage required for the cation to be reduced to its simple substance; The time of the initial electrolysis is 0.5 to 4 hours; The auxiliary electrode potential of the initial electrolysis is 2.0-3.8V.

5. The method for preparing a porous nano-silicon negative electrode material according to claim 4, characterized in that: The temperature of the high-frequency pulse electrolysis in step 1) is 500-1200° C.; The minimum potential of the high-frequency pulse electrolysis is 0.01 to 2 V greater than the theoretical decomposition voltage of cations in the molten salt, and the potential difference between the maximum potential and the minimum potential is 0.1 to 4 V; The time of the high-frequency pulse electrolysis is 1 to 6 hours, and the duration of each band of the high-frequency pulse electrolysis is 25 to 50 seconds; The auxiliary electrode potential of the high-frequency pulse electrolysis is 2.5-5V.

6. The method for preparing a porous nano-silicon negative electrode material according to claim 4 or 5, characterized in that: The alloy homogenization treatment in step 2) includes a first stage of preliminary homogenization treatment, a second stage of target phase homogenization treatment, and a third stage of cooling treatment; The heating rate of the first stage of preliminary homogenization treatment is 1-5°C / min, the target temperature is 650-1100°C, and the holding time is 30-300min; The temperature change rate of the target phase homogenization treatment in the second stage is 1-5°C, the target temperature is 700-1200°C, and the holding time is 20-200min; The cooling rate of the third stage cooling treatment is 1-5°C / min, and the target temperature is 500-1200°C.

7. The method for preparing a porous nano-silicon negative electrode material according to claim 6, characterized in that: The temperature of the electrolytic dealloying treatment in step 3) is 500-1200° C., the electrolytic voltage of the electrolytic dealloying treatment is 0.5-3.8 V, and the time of the electrolytic dealloying treatment is 0.5-6 h; The potential of the auxiliary electrode in the electrolytic dealloying treatment is 1.5 to 3.0V.

8. The method for preparing a porous nano-silicon negative electrode material according to claim 7, characterized in that: The annealing temperature in step 3) is 300-900° C., and the annealing time is 60-300 min.

9. The porous structure nano-silicon negative electrode material prepared by the method for producing a porous structure nano-silicon negative electrode material according to any one of claims 1 to 8.

10. Use of the porous structure nano-silicon negative electrode material according to claim 9 in negative electrode materials for lithium batteries.

Citation Information

Cited By

  • Layered silicon material and preparation method and application thereof

    CN122126852A